2019
DOI: 10.1039/c9ta07697b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced catalytic activity of nanostructured, A-site deficient (La0.7Sr0.3)0.95(Co0.2Fe0.8)O3−δ for SOFC cathodes

Abstract: Significant enhancement in the catalytic activity of the benchmark (LaSr)(CoFe)O3−δ (LSCF) electrode is obtained by modifying the A-site non-stoichiometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 57 publications
0
35
0
Order By: Relevance
“… 59 Our recent work on CoFeO x (B-site) precipitation in the A-site deficient (La 0.7 Sr 0.3 ) 0.95 Co 0.2 Fe 0.8 O 3 (LSCF) showed that nanoscale B-site oxides decorated the surfaces of LSCF, and thus lead to increased catalytic activity for ORR. 7 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 59 Our recent work on CoFeO x (B-site) precipitation in the A-site deficient (La 0.7 Sr 0.3 ) 0.95 Co 0.2 Fe 0.8 O 3 (LSCF) showed that nanoscale B-site oxides decorated the surfaces of LSCF, and thus lead to increased catalytic activity for ORR. 7 …”
Section: Resultsmentioning
confidence: 99%
“… 3 Therefore, thermally induced transformations occurring at the nanometer scale and below must be taken into account as they can be detrimental to the catalytic activity, including the segregation of inactive phases toward the surfaces, 4 particle formation and coarsening, 5 phase transitions, and decomposition at high temperatures. 6 The preparation technique, 7 coating conditions [substrate temperature ( T substrate ), background oxygen pressure ( p O 2 ) etc. ], 8 crystallization behavior, 9 and thermal history 10 of the samples have been shown to influence the electrochemical activity but often remain unreported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…56,57 However, deliberate A-site deciency tends to be 5-20%, not the 30-40% as observed here (although our result were only measured across a depth of only a few (10-20) unit cells), as the stability of these materials is generally dependant upon a narrow range of the A : B site ratio. 58 The sub-surface of other perovskite materials have been shown to decompose into the Ruddleston-Popper type layered perovskite and spinel phases as a result of changing stoichiometry. 59,60 However, at this time, it is unclear whether the sub-surface of LSCF underwent a phase change from the observed A-site deciency.…”
Section: Oxygen Transportmentioning
confidence: 99%
“…For this reason, finding more suitable cathode electrocatalysts with superior electrocatalytic activity is essential. ABO 3 type mixed ion-electron conductors (MIECs) have become extensively discussed cathode electrocatalysts because of their high doping flexibility and ex-cellent catalytic activity, e.g., La x Sr 1-x Co y Fe 1-y O 3-δ [3,4], Ba x Sr 1-…”
Section: Introductionmentioning
confidence: 99%